Hubungan Pemakaian Kontrasepsi Suntik 1 Bulan Terhadap Perubahan Berat Badan Di Desa Buluh Kecamatan Socah Kabupaten Bangkalan - Riski Fitriyatul Fitriyatul (Universitas Muhammadiyah Surabaya, 2022)
Objective: The purpose of this study was to know the relationship between the usage of 1-month injection contraception to chains in body weight at Desa Buluh Kecamatan Socah Kabupaten Bangkalan.Methods: This study was analyzed using by cross-sectional approach. The sample was 1-month injection contraception acceptors at Desa Bluh Kecamatan Socah Kabupaten Bangkalan amounts 30 respondents that were chosen by purposive sampling.Results: The technique of data analysis done by Rank Spearman, shown 16 respondents (53.3%) used 1-month injection contraception regularly, and 16 respondents (53.3%) did not experience body weight change. Conclusion: There was a relationship between the usage of 1-month injection contraception to changes in body weight at Desa Buluh Kecamatan Socah Kabupaten Bangkalan